Social Security : The Story of British Social Progress and the Beveridge Plan - Great Britain. Inter-departmental Committee on Social Insurance and Allied Services; Davison, Ronald C. (Ronald Conway), 1884- (London : G.G. Harrap and Co., 1943)
1943 1943 1940s 3 preliminary leaves, 9-62 pages : illustrations, diagrams THE STORY OF BRITISH SOCIAL PROGRESS AND THE BEVERIDGE PLAN CHAPTER I BRITAIN'S SOCIAL PROGRESS REVIEWED (I) BACKGROUND TO THE PRESENT SCENE At the start of the present century Britain was coming to realize that poverty and want in an industrial community were not just part of the natural order of things, but could be prevented by social action. In forty years this realization has led to a profound improvement in our standards of living. A steady stream of social legislation since 1906 has gone far to transform the lives of the great mass of our people ; they are to-day better educated, better housed, and healthier ; they have more leisure and are longer lived than ever before. There is still a submerged class in our city slums, but it is far smaller than it used to be. The first charts or diagrams in this book reveal clearly our past progress in these respects. They do so because this is the proper background against which the further necessary reforms ought to be viewed. At present the Beveridge Plan, in its main provisions holds the field of reform. That plan is not a bolt from the blue ; it does not propose a sudden or total revolution in British social life. On the contrary, it grows naturally out of our 9 15X/2/566/303